2019
DOI: 10.1177/1526602819826593
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Care for Critical Limb Ischemia: Current Gaps and Opportunities for Improvement

Abstract: Critical limb ischemia (CLI), defined as ischemic rest pain or nonhealing ulceration due to arterial insufficiency, represents the most severe and limb-threatening manifestation of peripheral artery disease. A major challenge in the optimal treatment of CLI is that multiple specialties participate in the care of this complex patient population. As a result, the care of patients with CLI is often fragmented, and multidisciplinary societal guidelines have not focused specifically on the care of patients with CLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 98 publications
0
21
0
2
Order By: Relevance
“…They include but are not limited to atherectomy and cutting/scoring/focal force devices. [97][98][99][100] The proposed mechanism of these techniques is to increase target lesion compliance, thereby reducing the risk of flow-limiting dissection and improving the immediate results of BA. 101 Cutting and scoring balloons may improve the outcomes of angioplasty compared with standard BA.…”
Section: Residual Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…They include but are not limited to atherectomy and cutting/scoring/focal force devices. [97][98][99][100] The proposed mechanism of these techniques is to increase target lesion compliance, thereby reducing the risk of flow-limiting dissection and improving the immediate results of BA. 101 Cutting and scoring balloons may improve the outcomes of angioplasty compared with standard BA.…”
Section: Residual Stenosismentioning
confidence: 99%
“…Currently no standard exists for the treatment of infrapopliteal lesions, and as such treatment approaches in a systematic manner are missing from clinical practice. 98 The authors propose an optimal BA algorithm ( Figure 3) that includes (1) assessment of vessel calcification, (2) optimal balloon sizing, (3) prolonged balloon inflation, and (4) assessment of postangioplasty dissection and recoil. The goal of this algorithm is to optimize each step in angioplasty treatment and thereby ultimately improve patency.…”
Section: Optimal Ba For Infrapopliteal Lesions: a Proposed Algorithmmentioning
confidence: 99%
“…CLI-specific antiplatelet/anticoagulant therapy is mainly extrapolated from studies of patients with asymptomatic PAD or claudication [27, 47]. Azarbal et al suggested the extrapolation of PAD to CLI is reasonable since the studies contain both PAD and CLI patients [27]; however, there are challenges with this extrapolation.…”
Section: Discussionmentioning
confidence: 99%
“…34 Thus, vessel calcification is directly correlated to the overall implications of PAD. 35 , 36 As such, numerous treatment methods have been developed for plaque modification before angioplasty 31 , 37 41 in order to minimize periprocedural complications, enhance vessel patency, and minimize the need for provisional stenting. 42 …”
Section: Introductionmentioning
confidence: 99%